Evaluation of clinical effectiveness of topical 0.2% glyceryl trinitrate, topical 2% diltiazem and their combination in the treatment of chronic anal fissure - Rayamajhi, Bikash Bahadur; Khadka, Anjan; Thakali, Kabir; Thapa, Bikash Bikram; Thapa, Narayan; Bhandari, Bharat Bahadur (Journal of Kathmandu Medical College, 2020)
Background: The longitudinal tear or defect in the epithelial lining of the anal canal distal to the dentate line is called anal fissure. It is of two types: acute and chronic. The break in the cycle of pain, spasm and ischemia is essential for successful treatment of anal fissure. Among multiple non-surgical treatment approaches, the appropriate approach with good patient compliance might be the use of topical agents as chemical sphincterotomy. However, the effectiveness of these agents has not been evaluated widely. Objectives: To evaluate clinical effectiveness of topical 0.2% glyceryl trinitrate, topical 2% diltiazem and their combination in the treatment of chronic anal fissure. Methodology: The study was prospective comparative type including total 158 patients. Initially, they were given first line therapy followed by chemical sphincterotomy agents. The study drugs were given to 84 patients (three groups - 0.2% glyceryl trinitrate, 2% diltiazem and their combination) who were not healed after initial therapy. Patients were assessed for pain using visual analogue scale and other symptoms prior to and after two and six weeks of therapy. Results: Complete healing rate was higher with combination (92.86%) than individual agents. The reduction of visual analog scale score within each group and between the groups in the period between before and after treatment was found to be statistically significant. Headache and hypotension were the common side effects seen during study. Conclusion: Anal fissures can be successfully managed by chemical sphincterotomy. The topical nitrates and calcium channel blockers in combination are found to be effective choice rather than individual agents.